Yield Components and Efficiency Index of Maize Yield: Relationship to Yields in Tidal Fields - Yustisia Yustisia; NP Sri Ratmini; J Amirrullah; Y Juwita; YPAP Hutabarat; Atekan Atekan (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Identification of the advantages of hybrid maize lines is needed to support the increased production and development of maize in tidal fields. This study aimed to identify the agronomic characters and yield components of hybrid maize lines/varieties and their relationship with high yield and efficient fertilization in tidal fields. The design used was a Split Plot with three replications. The Main Plot was a hybrid maize line/variety (L39/MR4, MGOLD/G8, G28/MGOLD, P27). The subplots were Composite Fertilizer with 2 measures, namely 600 kg/ha and 720 kg/ha. The fertilizers of Urea (50%), SP 36 and NPK (100%) were given at 10 days after planting (DAP). The remaining Urea was given at 30 DAP, 50% and 58.33% respectively in the Composite Fertilizer treatment of 600 kg/ha and 720 kg/ha. The technical culture applied was optimum tillage with the 70 cm x 25 cm spacing, the irrigation being carried out at D/DAP and 15 DAP, the optimal control on the weed and Plant Pest Organisms. The result showed that the number of rows/cobs was an alternative variable in identifying maize lines/varieties with high yield and efficient fertilization. This character was closely correlated with seed/ear weight (r = 0.94) and Grain Yield Efficiency Index/GYEI (r = 0.84). All Genotypes were nutrient efficient (GYEI > 1) except G28/MGOLD (IGYEI < 1). Another approach used to identify efficient fertilization lines/varieties was the variable percentage of yield reduction through regression equations with GYEI (y = - 0.0104 x + 1.0426). The character of high number of rows/cob could be used as genetic material in plant breeding programs. The lines/varieties as a component of efficient technology and high productivity would contribute to increase production and development of maize in tidal fields.